Study of Public Knowledge on the Use of Herbal Medicines and Their Interactions - Judijanto, Loso (Pt. Anagata Sembagi Education, 2025)
The use of herbal medicines has increased significantly in the past two decades, particularly in developing countries like Indonesia. This phenomenon is largely influenced by the perception that herbal medicines are safer due to their natural nature, although public understanding of scientific aspects, such as dosage, drug interactions, and side effects, remains very limited. Various studies have shown that combinations of herbal and conventional medicines, such as ginkgo biloba with anticoagulants or St. John's wort with antidepressants, can cause dangerous pharmacological interactions, including toxicity and decreased therapeutic efficacy. The lack of formal health education and the dominance of information from social media and advertising exacerbate misinformation in the community. Furthermore, many health workers have not received training in herbal pharmacology, thus preventing them from providing optimal evidence-based education. Weak regulations on the distribution and labeling of herbal products also contribute to the risk of unsafe self-medication practices. This study used a literature review with a qualitative-descriptive approach to assess the level of public knowledge and the risks of herbal drug interactions. The results are expected to form the basis for the development of integrative educational and regulatory policies to improve public health literacy and ensure safer, more rational, and evidence-based use of herbal medicines.